Optimalisasi Metode Timbang Terima Berbasis SBAR dalam Upaya Peningkatan Keselamatan Pasien di Ruang Rawat Inap - Hendry Kiswanto Mendrofa; Dwi Astuti; Elisabeth Bre Bolly; Alfonso Rahangmetan; Lusia Komsari; Obeth Noriwari (I-Com: Indonesian Community Journal, 2023)
Handover implementation can provide clear information on patient care during the previous shift so that nurses know about efforts to continue the care provided and improve patient safety. The aim of this activity is to be able to implement the handover process using SBAR communication techniques optimally in the inpatient room. This service activity occurred at Jayapura District Hospital in April - August 2023. The target of this activity was nurses in the Inpatient Room. The method of this activity is through socialization, role play, determining the person in charge, preparing formats and technical instructions, preparing management cases, determining implementation schedules, and documenting results. Based on the results of the activities carried out, 24 nurses experienced an increase in knowledge and there were 4 nurses who did not experience a change in their scores. Optimization of patient handover activities can be realized if leadership supervises and ensures weighing activities comply with operational standards.